POV-6 Evaluation of high energy pulsed light in combination with an essential oil in vapor phase to decontaminate chia seeds (Salvia hispanica L). - Reyes-Jurado, Fátima; Guzmán-Flores, Miguel Alejandro; Ramirez-Hernandez, Johana; Bárcena-Vicuña, Guadalupe Gabriela; López-Malo, Aurelio; Ávila-Sosa, Raúl (Revista Productos Naturales, 2022)
Due to the demand for fresh and minimally processed foods, alternatives to traditional methods are currently being explored. Among the emerging technologies proposed are the use of high hydrostatic pressure, ultrasound, high intensity pulsed light as well as the use of natural antimicrobials.